(untitled) - Boggs , Joseph M. (Boston, 2008)
This introduction to film appreciation uses both contemporary and classic movies to help students develop critical skills in the analysis and evaluation of film. By suggesting what to look for and how to look for it, the text challenges students to sharpen their powers of observation, establish habits of perceptive watching, and discover complex aspects of film art that will further enhance their enjoyment of watching films. In addition it makes the link from literature to film in chapters on Thematic Elements, Fictional and Dramatic Elements and a unique chapter on Adaptions.
Keywords: Film criticism,Phê bình phim